Phenolics Content and DPPH Free Radical Scavenging Activity of Dalbergia latifolia leaf ethanolic extract - Masendra Masendra; Agus Ngadianto; Ridla Arifriana; Greitta Kusuma Dewi; Eko Prasetyo; Muhammad Rafly Nugraha; Saffana Ahda Labiba; Fatimah Ayu Warahapsari; Brandon Aristo Verick Purba; Ganis Lukmandaru (Wood Research Journal, 2022)
Dalbergia latifolia is one of the famous species that naturally grows in Java, Indonesia. The wood of this species is purple in color and the leaf is utilized as forage. The purpose of this study is to determine the bioactivity and phenol contents of D. latifolia leaf ethanolic extract. The antioxidant activity and anti-termite activity were measured through the DPPH method and Neotermes bosei activity. Furthermore, phenol contents were determined through colorimetric method and ethanolic extract constituents were identified by GC-MS. The DPPH inhibition of ethanol extract of D. latifolia leaf exhibited 138.20±2.14 µg/ml. While the measurement of total phenol and total flavonoid content of D. latifolia leaf showed a value of 192.67±9.41 mg GAE/ g and 55.23±5.11 mg QE/ g of dried extract sample. The termiticidal activity of ethanolic extract showed low activity. The GC-MS detection showed fatty acids as dominant compounds. The inhibition of DPPH by D. latifolia leaf ethanol extract in this study suggested this leaf is potent as antioxidant agents.